The candid life of Meena Dave : a novel - Patel, Namrata (2022)
"A woman embarks on an unexpected journey into her past in an engrossing novel about identity, family secrets, and rediscovering the need to belong. Meena Dave is a photojournalist and a nomad. She has no family, no permanent address, and no long-term attachments, preferring to observe the world at a distance through the lens of her camera. But Meena's solitary life is turned upside down when she unexpectedly inherits an apartment in a Victorian brownstone in historic Back Bay, Boston. Though Meena's impulse is to sell it and keep moving, she decides to use her journalistic instinct to follow the story that landed her in the home of a stranger. It's a mystery that comes with a series of hidden clues, a trio of meddling Indian aunties, and a handsome next-door neighbor. For Meena it's a chance for newfound friendships, community, and culture she never thought possible. And a window into her past she never expected. Now as everything unknown to Meena comes into focus, she must reconcile who she wants to be with who she really is"--Page 4 of cover.
Keywords: Identity (Psychology) -- Fiction; Family secrets -- Fiction; Photojournalists -- Fiction; East Indian Americans -- Fiction